Acute dichromate poisoning following the use of toxic purgatives - Wood, Robin (Department of Medicine, 2020)
During the last ten years, several patients have presented to the Renal Unit of Groote Schuur Hospital with acute renal failure following the use of traditional (N'anga or Gqirha) medication. The history together with abnormal liver-function tests and renal failure was thought to be suggestive of a toxic aetiology. The specific toxin however remained unknown, until during the admission of one patient, a relative brought in the medication, analysis of which revealed a high concentration of potassium dichromate. Subsequently elevated levels of chromium were demonstrated by atomic absorption spectrometry in the blood and urine of this patient. Following this case there have been six further cases of acute renal failure resulting from use of dichromate containing traditional remedies. These remedies were obtained from a variety of sources including street-hawkers, herbal chemists, and traditional healers. Clinical and laboratory data relating to these seven patients will be presented.